5-Hydroxymethylfurfural (HMF) formation, occurrence and potential health concerns: recent developments. (2nd October 2021) - Choudhary, Ankit; Kumar, Vikas; Kumar, Satish; Majid, Ishrat; Aggarwal, Poonam; Suri, Sheenam
Abstract: 5-Hydroxymethylfurfural (HMF) is synthesized by the thermal decomposition of the sugars. Numerous types of food products are having a significant amount of HMF. Besides the thermal processing, other food processing methods (drying and dehydration, roasting, baking and storage of the product) are important factors for the synthesis of the HMF. HMF possesses different health effects including positive and negative health effects. Only few regulatory bodies have issued the guidelines and limits related to HMF. The present review has been planned to explore the HMF in terms of synthesis, occurrence, the effect of food processing, health effects and the safety guidelines.